Diabetes complications in childhood and adolescent onset type 2 diabetes—a review - Amutha, Anandakumar; Mohan, Viswanathan (Journal of diabetes and its complications, 2016)
Diabetes mellitus is one of the most common endocrine disorders in children. Earlier, diabetes in children was almost exclusively type 1 diabetes. Recently, the scenario has changed and increasing numbers of children and adolescent T2DM are being diagnosed. As the epidemic of T2DM shifts to children and adolescents, there is an increased risk of development of micro and macrovascular complications. This could potentially affect the economy of the nation apart from posing a large burden to the individual and his or her family. Prevention and treatment are especially important, given the fact that onset at an early age increases the risk of developing micro and macrovascular complications due to increased duration of exposure to hyperglycemia and other metabolic abnormalities. Diagnosing children and adolescents with T2DM early and instituting good control of all risk factors could yield good results in the prevention of long term complications of diabetes. This review focuses on the prevalence of complications of diabetes among children and adolescents with T2DM.